2021
DOI: 10.7554/elife.71179
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of brilliant iridescent feather nanostructures

Abstract: The brilliant iridescent plumage of birds creates some of the most stunning color displays known in the natural world. Iridescent plumage colors are produced by nanostructures in feathers and have evolved in diverse birds. The building blocks of these structures—melanosomes (melanin-filled organelles)—come in a variety of forms, yet how these different forms contribute to color production across birds remains unclear. Here, we leverage evolutionary analyses, optical simulations, and reflectance spectrophotomet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 61 publications
2
17
0
Order By: Relevance
“…Figure a is obtained for a reference case (no hybridization), in which the nanocube directly sits on a semi-infinite SiO 2 substrate. Consistent with earlier works on plasmonic color generation, , both the real and imaginary parts of ED eigenfrequency λ̃ ED largely vary. Notably, Re­(λ̃ ED ) spans almost the entire visible spectral domain, Re­(Δλ̃ ED ) ≈ 200 nm.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…Figure a is obtained for a reference case (no hybridization), in which the nanocube directly sits on a semi-infinite SiO 2 substrate. Consistent with earlier works on plasmonic color generation, , both the real and imaginary parts of ED eigenfrequency λ̃ ED largely vary. Notably, Re­(λ̃ ED ) spans almost the entire visible spectral domain, Re­(Δλ̃ ED ) ≈ 200 nm.…”
Section: Resultssupporting
confidence: 84%
“…50−52 For instance, for color generation with Mie or plasmonic resonances, small size or shape variations of the constituent nanoparticles lead to significant color changes. 2,53 Despite significant size or shape dispersions and occasional particle aggregation (see the statistical analysis in the top inset in Figure 6) quantitative agreement is achieved between the measurements and our theoretical predictions based on a monodisperse approximation (Figures 5a and S5.1). This suggests that the present samples are exceptionally resilient to fabrication imperfections.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…Some studies have suggested that the keratin cortex surrounding multilayered melanosomes affects the colours of bird feathers [16,37,38,45]. Of these, most have considered keratin cortices of different thicknesses with theoretical models [36][37][38]46], statistical analyses [33,45] and by observing barbule samples where the keratin cortex had been accidentally removed [36,37]. Specifically, based on a quantitative optical modelling of multi-layered melanosomes in mallard barbules-a very similar system to the pheasant feathers examined in this study-Stavenga et al [38] have convincingly explained the effect of changing barbule cortex thickness on the iridescent colours produced by multi-layered melanosomes on the hue.…”
Section: Discussionmentioning
confidence: 99%
“…More saturated colours can be produced by increasing the difference between the refractive indices, the degree of order or the thickness of optical nanostructures [29][30][31][32]. Moreover, the varying shapes of the melanosomes (solid rods, hollow rods, solid platelets or hollow platelets) also play a significant role in producing structural colours, as they can vary refractive index profiles [32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%